A Comparative Study Of Caudal Epidural Block Versus Ultrasound-Guided Ilioinguinal-Iliohypogastric Nerve Block For Postoperative Analgesia In Older Children Undergoing Inguinal Surgeries - M, Murali Manoj.; R, Prashanthi.; G, Vignesh.; V, Sasikumar. (Journal of Neonatal Surgery, 2025)
Background: Effective postoperative pain control in pediatric inguinal surgeries is crucial for enhanced recovery and patient comfort. While caudal epidural block has long been the standard regional technique, ultrasound-guided ilioinguinal-iliohypogastric (USG II/IH) nerve block has recently gained traction due to its precision and safety. This study compares the efficacy and safety of caudal block versus USG II/IH block in older children undergoing elective inguinal procedures. Methods: A prospective, randomized, comparative clinical study was conducted on 60 children aged 6–12 years, ASA I–II, scheduled for unilateral herniotomy or orchidopexy under general anesthesia. They were randomized into two groups: Group C (caudal block, n=30) received 1 mL/kg of 0.25% bupivacaine, and Group I (USG II/IH block, n=30) received 0.2 mL/kg of 0.25% bupivacaine. Primary outcome measured was duration of postoperative analgesia. Secondary outcomes included FLACC pain scores at 1, 2, 4, and 6 hours post-op, need for rescue analgesia, intraoperative hemodynamic stability, and any complications. Results: Demographic variables and baseline characteristics were statistically comparable between the groups. Group I exhibited significantly longer duration of analgesia (6.78 ± 1.03 hours) than Group C (4.12 ± 0.85 hours; p < 0.0001). FLACC scores were significantly lower in Group I at all time points (1, 2, 4, 6 hours; p < 0.001). Rescue analgesia requirement was lower in Group I (40%) compared to Group C (70%; p = 0.015). Complications such as motor block and urinary retention occurred in 10% of Group C but were absent in Group I. Hemodynamic parameters remained stable and comparable in both groups. Conclusion: Ultrasound-guided ilioinguinal-iliohypogastric block provides superior and longer-lasting postoperative analgesia with fewer complications than caudal block in older children undergoing unilateral inguinal surgeries, making it a preferable regional anesthetic technique in this population.